Direct Effect of Using Kinesio Taping (KT) on Balance in Young People - Pertiwi, Jasmine; Ghufroni, Afif (Jurnal Keterapian Fisik, 2025)
Background: This study investigated the immediate effects of the Kinesio Taping (KT) mechanical correction technique on balance, joint mobility, and muscle strength in healthy young adults. The findings aim to clarify whether this taping method can contribute to improved postural control and functional performance in individuals without musculoskeletal disorders. The purpose of this study: was to examine the immediate effects of kinesio taping on balance among adolescents. Methods: A pre-experimental, one-group pre- and post-test design was employed. Accidental Sampling technique 106 healthy individuals aged 18-25 years (20 males, 86 females) participated. KT was applied to the gastrocnemius, soleus, and Achilles tendons using specific techniques (10-50% stretch for gastrocnemius, Method I for Achilles, and Y method for gastrocnemius). Balance was evaluated through the Star Excursion Balance Test (SEBT), which measures reach distance in eight specific directions. Range of motion and muscle strength were also examined and differences before and after the KT intervention were analyzed using a paired sample t-test. Results: The participants had an average age of 19.20 years and a mean BMI of 21.63. Pre-intervention SEBT scores ranged from 38 to 84 (mean = 55.48, SD = 8.733), while post-intervention scores ranged from 37 to 79 (mean = 59.06, SD = 10.068). A paired sample t-test demonstrated a statistically significant improvement in SEBT scores following the KT intervention (p < 0.001), indicating enhanced balance performance after taping. Conclusion: This study indicates that applying KT’s “mechanical correction” technique to the ankle joint can immediately enhance dynamic balance in healthy young adults. These results highlight the potential role of KT as a supportive intervention to improve balance and possibly minimize the risk of injury.